Fish Loss/Waste and Low-Value Fish Challenges: State of Art, Advances, and Perspectives - Angela Racioppo; Barbara Speranza; Daniela Campaniello; Milena Sinigaglia; Maria Rosaria Corbo; Antonio Bevilacqua (Foods, 2021)
The sustainability of fishery is a global challenge due to overfishing and reduced stocks all over the world; one of the leading factors of this threat is fish loss/waste. As a contribution to the global efforts towards a sustainable world, this review addresses the topic from different sides and proposes an overview of biorefinery approaches by discussing bioactive compounds that could be produced from fish loss (nitrogen compounds, lipids, minerals and pigments, and fish-based compounds such as chitosan). The second part of this review reports on the possibility of using loss or unwanted fish to design products for human consumption or for animal feeding, with a focus on economic criteria, consumers’ segmentation, and some examples of products. The final focus is on Food and Agriculture Organization FAO guidelines as a roadmap for the future with respect to solving this threat by addressing the problem from different sides (technology, skills, market, policy, social and gender equity, and infrastructures).